2022
DOI: 10.1289/ehp10291
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study on the Impact of Indoor Temperature on Heat-Related Symptoms in Older Adults Living in Non–Air-Conditioned Households

Abstract: Background: Both chronic and acute heat result in a substantial health burden globally, causing particular concern for at-risk populations, such as older adults. Outdoor temperatures are often assessed as the exposure and are used for heat warning systems despite individuals spending most of their time indoors. Many studies use ecological designs, with death or hospitalizations rates. Individual-level outcomes that are directly related to heat-symptoms should also be considered to refine preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…This temperature was chosen based on indoor temperatures measured in the homes of older adults during hot summer days in Detroit. 20 It is also comparable to conditions measured in non-air-conditioned homes in Montérégie, Quebec, Canada (warm summer continental climate, Köppen Subtype Dfb, from Ottawa) 21 and in low-rent share housing (doss-houses) occupied by older adults in Seoul, South Korea (hot summer continental climate, Köppen subtype Dfw, from Ottawa). 34 36°C, 45% relative humidity (heat index: 41°C) to simulate peak indoor temperatures during extreme heat waves when ambient cooling (e.g., air conditioning) is unavailable or otherwise not used.…”
Section: Methodssupporting
confidence: 63%
See 3 more Smart Citations
“…This temperature was chosen based on indoor temperatures measured in the homes of older adults during hot summer days in Detroit. 20 It is also comparable to conditions measured in non-air-conditioned homes in Montérégie, Quebec, Canada (warm summer continental climate, Köppen Subtype Dfb, from Ottawa) 21 and in low-rent share housing (doss-houses) occupied by older adults in Seoul, South Korea (hot summer continental climate, Köppen subtype Dfw, from Ottawa). 34 36°C, 45% relative humidity (heat index: 41°C) to simulate peak indoor temperatures during extreme heat waves when ambient cooling (e.g., air conditioning) is unavailable or otherwise not used.…”
Section: Methodssupporting
confidence: 63%
“…Consistent with these findings, Teyton et al. 21 reported progressive increases in the incidence of heat-related symptoms (e.g., thirst, reduced urine output, headache, nausea) with elevations in indoor ambient temperature in older persons living in Montérégie, Quebec, Canada (warm summer continental climate, Köppen Subtype Dfb, from Ottawa). These reports, when considered alongside the current data, support a 26°C indoor temperature limit for reducing physiological strain and discomfort and protecting health and well-being for individuals living in continental climates, 15 like those characterizing large areas of North America and Europe.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Due to declining physical health and thermoregulatory function, older adults are more susceptible to heat-related symptoms versus younger adults (e.g., heat syncope, heat cramps; Teyton et al, 2022 ). Research found that increased ambient temperature in Hong Kong from 2000 to 2016 was associated with higher risk of acute psychiatric disorder episodes in adults aged 65 years and older ( Qiu et al, 2022 ).…”
mentioning
confidence: 99%